Ethnobotanical Survey of Plants Used for the Treatment and Management of Sexually Transmitted Infections in Ibadan, Nigeria - Gbadamosi, Idayat Titilayo (Ethnobotany Research and Applications, 2014)
<!–[if gte mso 9]> <![endif]–> In Nigeria, the prevalence of sexually transmitted infections (STIs) is fueled by low socioeconomic status and literacy levels. Although phytomedicine is part of Nigerian culture, the use of herbs in STIs has become accentuated by low income status of people, inadequate health care delivery system, and the resistance of pathogenic organisms to orthodox drugs. A survey of medicinal plants used in the treatment of STIs was conducted with a goal of preserving indigenous knowledge and providing a list of plants for future research for potential drug production. A questionnaire-guided survey of three Local Government Areas (LGAs) of Ibadan, Nigeria, was randomly conducted on 300 respondents who were knowledgeable in ethnomedicine for information on their prescriptions for the treatment of STIs. Based on the responses obtained, 52 prescriptions or formulations were recorded for gonorrhea, candidiasis, vaginitis, syphilis, HIV/AIDS, and STI-associated skin infections. The study newly revealed the use of leaves of Ageratum conyzoides (L.) L. and Nicotiana tabacum L. in the management and treatment of HIV/AIDS. Findings of the present ethnobotanical survey will be beneficial in general health care, ecological control, forest conservation, biotechnology research, and in providing leads to medicinal plants from which potential new drugs may be developed. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>